Nursing strategies after pancreaticoduodenectomy: continuity of care combined with immunomodulatory nutrition - Feng, Xiaodong; Li, Wei; Tang, Yufu; Han, Lei; Bi, Ting; Zhang, Wei; Miao, Yuqing (Frontiers in Surgery, 2025)
BackgroundPancreaticoduodenectomy (PD) is a highly invasive procedure with a long operation time, resulting in a high incidence of postoperative complications. The quality of patient care remains a key factor in improving prognosis. This study aimed to evaluate the impact of continuity of care combined with immunomodulatory nutrition on the postoperative recovery and quality of life of patients undergoing PD surgery.MethodsThis was a randomized controlled study involving 120 patients who underwent PD surgery at our hospital between February 2022 and February 2024. The patients were randomly divided into the conventional care group (CG) and the intervention group (IG), with the latter receiving continuity of care combined with arginine-rich immunonutritional support. The main observation indicators included survival analysis, recovery of gastrointestinal function, length of hospital stay, nutritional status, immune function, postoperative complications, negative emotions and quality of life.ResultsThere was no significant difference in the overall survival rate between the two groups. Compared with the CG, the IG had shorter length of hospital stay, better recovery of gastrointestinal function, better improvements of nutritional indicators such as ALB and PAB, lower levels of pro-inflammatory factors TNF-α, IL-6 and CRP, better improvement of CD4+/CD8+ ratio, lower incidence of postoperative complications, lower SAS and SDS scores and better quality of life.ConclusionContinuity of care combined with immunomodulatory nutrition provides a strong rationale for postoperative care of PD, and is worthy of clinical promotion and practice. More clinical cases and long-term follow-ups are needed to further verify its effectiveness.